Optimizing Nitrogen and Water Use Efficiency in Wheat Cropping Systems Through Integrated Application of Biochar and Bokashi Under Different Irrigation Regimes - Gyanendra Dhakal; Takeshi Fujino; Srijana Thapa Magar; Yuji Araki (Nitrogen, 2025)
Addressing the challenge of reducing environmental pollution from agricultural practices by improving nitrogen use efficiency (NUE) and water use efficiency (WUE) while ensuring high crop yields is essential for sustainable agriculture. Using a controlled glasshouse experiment, we evaluated the combined effects of biochar and bokashi under different irrigation regimes on NUE, WUE, and yield-related parameters in a wheat cropping system. The experiment followed a completely randomized design with three replications with four treatments: (1) control (C), (2) bokashi only (B0), (3) bokashi +1% biochar (B1), and (4) bokashi +2% biochar (B2). These treatments were evaluated at three irrigation levels—30% (IR30), 50% (IR50), and 60% (IR60) of field capacity (FC), resulting in a total of twelve treatments. Co-application of bokashi–biochar significantly (p < 0.050) improved grain yield (GY), straw yield (SY), total biomass (TB), total nitrogen uptake (TNU), grain protein content (GPC), NUE, and WUE, with the most notable benefits observed at 1% biochar application compared to C and B0 treatments. In addition, both types of treatment (bokashi and bokashi with biochar) and the level of irrigation had a significant impact on GY, SY, TB, TNU, GPC, NUE, and WUE. The B1 and B2 treatments further improved yield and efficiencies compared to bokashi alone. The positive correlation between grain yield and WUE underscores the importance of optimizing irrigation strategies alongside soil amendments for improved crop productivity. These enhancements in yield and efficiency are likely attributed to the increased soil fertility, nutrient availability, and water retention resulting from the combination of biochar and bokashi.